Competition between diffusion and advection may mediate self-repair of wax microstructures on plant surfaces - Konrad, Wilfried; Neinhuis, Christoph; Roth-Nebelsick, Anita (Diffusion Fundamentals, 2016)
Cuticles are extracellular membranes covering the primary aerial parts of vascular plants. They consist of a multifunctional polymeric material with embedded soluble components, called waxes and serve as the interface between plants and their atmospheric environment, first of all protecting them from desiccation. Waxes are produced within the epidermal cells, then transported to the leaf surface and finally integrated into the polymer or deposited upon the cuticle. Remarkably, damaged wax layers may become repaired within a few hours. Base on an earlier hypothesis we present a theoretical framework explaining how waxes are transported through the plant epidermis by a combination of advection and diffusion. This combination suggests also a self-regulating repair mechanism, based on the assumption that intact cuticles induce an antagonistic equilibrium between advection and diffusion: whenever a wax layer is damaged, the equilibrium is disturbed in favour of advection, starting a repair process, which is intrinsically coming to an end after the cuticle has gained its original thickness.